AL-QUR’AN EDUCATIONAL PARK MANAGEMENT TO INCREASE THE QUALITY OF NON-FORMAL EDUCATION - Siti Sofihatun Rohmah; Milna Wafirah; Titis Rosowulan (Khidmatan, 2022)
The management of the Al-Qur’an Education Park in TPQ Jombong hamlet Paten Dukun is a way of managing a non-formal educational institution starting from planning, organizing, implementing, monitoring, and evaluating in order to achieve the goals of TPQ in Hamlet Jombong. The background in this study is that TPQ in Jombong Hamlet aims to educate children who are Qur’anic generations. Therefore, the TPQ in Jombong Hamlet requires management within the institution. This research aims to manage TPQ in Jombong Hamlet to maximize the purpose of an Al-Qur’an Education Park. This type of research uses descriptive qualitative. Data regarding the research sources were obtained through observation, interviews, and documentation of the implementation of activities at the Al-Qur’an Education Park in Jombong Hamlet. The results showed that the management of TPQ in Jombong Hamlet had not been carried out correctly. Therefore, with the research and service in Jombong Hamlet related to TPQ, it is hoped that it will be able to achieve the goals of TPQ itself and properly manage TPQ